Estrogen and progesterone promote breast cancer cell proliferation by inducing cyclin G1 expression - Tian,J-M. (2018)
Breast cancer is the most common cause of cancer among women in most countries (WHO). Ovarian hormone disorder is thought to be associated with breast tumorigenesis. The present study investigated the effects of estrogen and progesterone administration on cell proliferation and underlying mechanisms in breast cancer MCF-7 cells. It was found that a single administration of estradiol (E2) or progesterone increased MCF-7 cell viability in a dose-dependent manner and promoted cell cycle progression by increasing the percentage of cells in the G2/M phase. A combination of E2 and progesterone led to a stronger effect than single treatment. Moreover, cyclin G1 was up-regulated by E2 and/or progesterone in MCF-7 cells. After knockdown of cyclin G1 in MCF-7 cells using a specific shRNA, estradiol- and progesterone-mediated cell viability and clonogenic ability were significantly limited. Additionally, estradiol- and progesterone-promoted cell accumulation in the G2/M phase was reversed after knockdown of cyclin G1. These data indicated that estrogen and progesterone promoted breast cancer cell proliferation by inducing the expression of cyclin G1. Our data indicated that novel therapeutics against cyclin G1 are promising for the treatment of estrogen- and progesterone-mediated breast cancer progression.